Nontoxic Targeting of Energy Metabolism in Preclinical VM-M3 Experimental Glioblastoma - Augur, Zachary M.; Doyle, Catherine M.; Li, Mingyi; Mukherjee, Purna; Seyfried, Thomas N. (Frontiers in Nutrition, 2018)
Introduction: Temozolomide (TMZ) is part of the standard of care for treating glioblastoma multiforme (GBM), an aggressive primary brain tumor. New approaches are needed to enhance therapeutic efficacy and reduce toxicity. GBM tumor cells are dependent on glucose and glutamine while relying heavily on aerobic fermentation for energy metabolism. Restricted availability of glucose and glutamine may therefore reduce disease progression. Calorically restricted ketogenic diets (KD-R), which reduce glucose and elevate ketone bodies, offer a promising alternative in targeting energy metabolism because cancer cells cannot effectively burn ketones due to defects in the number, structure, and function of mitochondria. Similarly, oxaloacetate, which participates in the deamination of glutamate, has the potential to reduce the negative effects of excess glutamate found in many brain tumors, while hyperbaric oxygen therapy can reverse the hypoxic phenotype of tumors and reduce growth. We hypothesize that the combinatorial therapy of KD-R, hyperbaric oxygen, and oxaloacetate, could reduce or eliminate the need for TMZ in GBM patients. Methods: Our proposed approach for inhibiting tumor metabolism involved various combinations of the KD-R, oxaloacetate (2 mg/g), hyperbaric oxygen, and TMZ (20 mg/kg). This combinatorial therapy was tested on adult VM/Dk mice bearing the VM-M3/Fluc preclinical GBM model grown orthotopically. After 14 days, tumor growth was quantified via bioluminescence. A survival study was performed and the data were analyzed and portrayed in a Kaplan Meier plot. Preliminary dosage studies were used and strict diet and drug administration was maintained throughout the study. Results: The therapeutic effect of all treatments was powerful when administered under KD-R. The most promising survival advantage was seen in the two groups receiving oxaloacetate without TMZ. The survival of mice receiving TMZ was diminished due to its apparent toxicity. Among all groups, those receiving TMZ had the most significant reduction in tumor growth. The most powerful therapeutic effect was evident with combinations of these therapies. Conclusion: This study provides evidence for a potentially novel therapeutic regimen of hyperbaric oxygen, oxaloacetate, and the KD-R for managing growth and progression of VM-M3/Fluc GBM.